Experimental study on improving the effect of microorganisms in solidifying fine-grained soil by red mud - Peng Liu; Yu Cheng; Guanghui Shao (Soils and Foundations)
To improve the reinforcement effect of MICP technology on fine-grained soil, and consider the fine particle size and activity characteristics of red mud, the experiment of red mud strengthening MICP solidified fine-grained soil was designed and carried out. Combined with mechanical test and microstructural analysis, the enhancing mechanism of red mud on microbial solidified fine-grained soil was comprehensively evaluated. The results show that: (1) Red mud can significantly improve the production of cement during microbial reinforcement of fine-grained soils; the optimal dosage of red mud is 20 %, which increases the strength by 34.6 % and the production of cement by 42.9 %, compared with conventional MICP. (2) After red mud was incorporated into the soil, the pore volume and pore diameter of the treated soil were significantly reduced, and the overall compactness was further improved. (3) The enhancement mechanism of microbial consolidation of fine-grained soils by red mud is mainly due to the presence of chemically active β-C2S and calcium oxide in red mud. These active calcium-based components undergo hydration and carbonation reactions under the action of microbial mineralization, generating calcium carbonate and hydrated calcium silicate, which improves the cement yield and enhances the intergranular bond strength, compactness and overall reinforcement effect of the treated soil.